The Role of Seaplane in Promoting the Concept of Sustainable Tourism in Indonesia - Prayitno, Hadi; Hariri, Ahmad; Rumani, Daniel Dewantoro; Luwihono, Andung; Wicaksono, Putra (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
This study discusses the role of amphibious aircraft in promoting the concept of sustainable tourism in Indonesia. Amphibious aircraft emerged as an innovative solution to the problem of accessibility to remote islands in Indonesia. However, the integration of amphibious aircraft into the Indonesian tourism sector and its alignment with the principles of sustainable tourism is a complex problem. This study uses a literature review research methodology. The analysis method used is descriptive qualitative. The descriptive qualitative research method is a method of seeking knowledge about previous research through books, national and international journals. During the review process, researchers look for similarities, find differences, provide opinions, summarize and combine into a new concept. This study aims to contribute knowledge and recommendations to policy makers, tourism operators, and environmental activists to support sustainable development in the Indonesian tourism sector. It is hoped that this study can provide a comprehensive picture of the potential benefits, challenges, and impacts of amphibious aircraft in promoting sustainable tourism practices in Indonesia, as well as identifying gaps and opportunities for future research.